High Performance Shortwave Infrared Organic Photodetectors Adopting Thiadiazole Quinoxaline‐Based Copolymers. Issue 19 (7th July 2022) - Park, Insun; Kim, Changki; Kim, Raesung; Li, Ning; Lee, Jaejun; Kwon, Oh Kyu; Choi, Byoungki; Ng, Tse Nga; Leem, Dong‐Seok
Abstract: Detection of light in the near‐infrared (NIR) and shortwave infrared (SWIR) spectral range is essential for the wide practical applications of biometrics, surveillance, machine vision, etc., in which organic molecules have gained growing interest as the potential sensing materials. In this study, the newly synthesized donor–acceptor type copolymers consisting of [1, 2, 5]thiadiazolo[3, 4‐g]quinoxaline core unit with phenyl pendant groups as the acceptor and thiophene unit as the donor for achieving high‐efficiency organic SWIR photodetectors are presented. A further variation of the alkoxy chain lengths in the core unit allows the optimized device to exhibit a high external quantum efficiency of 19.5%–21.7% at 1200 nm under the low reverse bias of −1 V, leading to a high detectivity up to 2.96 × 10 10 Jones for the spectral range beyond 1 µm. This further suggests the possible origin of the molecular structure‐dependent device performance in terms of the molecular stacking, morphological changes, and charge‐transporting properties in the bulk heterojunction blends. Abstract : Efficient [1, 2, 5]thiadiazolo[3, 4‐g]quinoxaline polymer‐based shortwave infrared organic photodiodes are demonstrated. By tuning the alkoxy chain length in the p‐type polymer core and blending with a non‐fullerene n‐type acceptor, a high external quantum efficiency of 19.5%–21.7% and a high specific detectivity of 8.17 × 10 9 – 2.96 × 10 10 Jones with −1 V reverse bias at 1200 nm wavelength are achieved.